Effects of Employee’s Empowerment on Organizational Commitment in Nepalese Organization - Shah, Aarati (Nepalese Journal of Economics, 2025)
This study examines the effects of employees’ empowerment on organizational commitment in Nepalese organization. Organizational commitment is the dependent variable. The selected independent variables are autonomy, rewards, communication, motivation and training. The primary source of data is used to assess the opinion of respondents regarding autonomy, rewards, communication, motivation, training and organizational commitment. The study is based on primary data of 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of effects of employees’ empowerment on organizational commitment in Nepalese organization. The study showed a positive impact of autonomy on organizational commitment. It indicates that autonomy in job leads to better organizational commitment. Similarly, the study showed a positive impact of rewards on organizational commitment. It indicates that better rewards attract employee to pursue commitment in interested field. Likewise, the study showed a positive impact of training on organizational commitment. It indicates that provides adequate training as per the necessity leads to increase in organizational commitment. Further, the study showed a positive impact of communication on organizational commitment. It indicates that flow of communication leads to make employees committed towards the organizations. In addition, the study showed a positive impact of motivation on organization commitment. It indicates that motivated employees are more committed towards the organization.